Yield curve control - Mika Kortelainen (Bank of Finland, 2020)
We study the yield curve control in Eurozone. We apply Chen, Cúrdia and Ferrero (2012) model that uses a financial friction to break Wallace's neutrality. We calibrate a bond supply shock that corresponds to the observed change in the time premium in euro area when the APP program was introduced. With some model simulations, we show that the effectiveness of both unconventional monetary policy and fiscal policy are enhanced, when the yield curve control is applied. Thus, we find that the yield curve control can be an effective tool, if applied in a credible manner for a long enough time period during an effective lower bound episode.
urn:nbn:fi:bof-202005282156
Keywords: E52; E58; 330; Yield curve control; monetary policy; fiscal policy; efficient lower bound; liquidity trap